2020
DOI: 10.3897/vcs/2020/48377
|View full text |Cite
|
Sign up to set email alerts
|

A phytosociological survey of aquatic vegetation in the main freshwater lakes of Greece

Abstract: Aims: This study aims to contribute to the knowledge of European freshwater lake ecosystems with updated and new information on aquatic plant communities, by conducting national-scale phytosociological research of freshwater lake vegetation in Greece. Moreover, it investigates the relationship between aquatic plant communities and lake environmental parameters, including eutrophication levels and hydro-morphological conditions. Study area: Lakes in Greece, SE Europe. Methods: 5,690 phytosociological relevés of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…In our results, however, we found that syntaxonomic richness followed a similar pattern to that of species richness (highly correlated), i.e., slightly higher numbers of plant communities were observed in lakes with moderate trophic levels, slightly lower numbers in lakes with low and high trophic levels, and significantly lower numbers in lakes with very high trophic levels. This result may be attributed to the fact that macrophyte communities contain a small number of taxa [55] and reinforces the "hump-back" model of diversity of macrophyte communities in lakes in the middle of the trophic gradient. However, variation in syntaxonomic richness values was also an issue for lakes with low and moderate trophic levels, reinforcing the need for the identification of parameters other than nutrient loading.…”
Section: Syntaxonomic Diversity Patternssupporting
confidence: 72%
See 1 more Smart Citation
“…In our results, however, we found that syntaxonomic richness followed a similar pattern to that of species richness (highly correlated), i.e., slightly higher numbers of plant communities were observed in lakes with moderate trophic levels, slightly lower numbers in lakes with low and high trophic levels, and significantly lower numbers in lakes with very high trophic levels. This result may be attributed to the fact that macrophyte communities contain a small number of taxa [55] and reinforces the "hump-back" model of diversity of macrophyte communities in lakes in the middle of the trophic gradient. However, variation in syntaxonomic richness values was also an issue for lakes with low and moderate trophic levels, reinforcing the need for the identification of parameters other than nutrient loading.…”
Section: Syntaxonomic Diversity Patternssupporting
confidence: 72%
“…In order to calculate syntaxonomic diversity, i.e., the richness of plant communities in each transect, we used the results of the phytosociological analysis in Zervas et al [55]. Each relevé was coded according to its community affiliation, and syntaxa richness in each transect was calculated using vegan package for R [54].…”
Section: Diversity Analysismentioning
confidence: 99%
“…The dominant species develops in several habitat types, often forming mono-paucispecific stands (Maiorca et al 2007;Sburlino et al 2004;Šumberová 2011a;Bolpagni and Piotti 2015;Spampinato et al 2019). The association can be found on marginal zone of still and nutrient-rich freshwater bodies, in very shallow sectors (Zervas et al 2020).…”
Section: Lemnetum Minoris Von Soó 1927 (Tablesmentioning
confidence: 89%
“…However, other authors, including Müller (1977), Scoppola (1982), andPott (1995), do not find the ground for the definition of a specific syntaxon due to the wide ecological and biogeographical values of this species (Sburlino et al 2004). The Lemnetum minoris is rather common in Europe including the Mediterranean area (Ninot et al 2000;Brullo et al 2002;Šumberová 2011a;Felzines 2012;Zervas et al 2020). The dominant species develops in several habitat types, often forming mono-paucispecific stands (Maiorca et al 2007;Sburlino et al 2004;Šumberová 2011a;Bolpagni and Piotti 2015;Spampinato et al 2019).…”
Section: Lemnetum Minoris Von Soó 1927 (Tablesmentioning
confidence: 99%
See 1 more Smart Citation